PENANGANAN JALAN DAN PEMASANGAN UTILITAS DI WILAYAH KOTA DENPASAR: KONDISI DAN KENDALA - Widhiyanasari, I.A; Parami Dewi, A.A. Diah; Dharmayanti, G.A.P Candra (JURNAL SPEKTRAN, 2017)
The road handling and installation of utilities in Denpasar City is still running based on the work program of each agency and has not been integrated. The authorities of the utilities repair and improve the network based on consumer demand, however, the implementation has not been integrated between the utilities installation and road handling program.  Consequently, the reinstatement of pavement conditions is not optimal and can potentially damage the utility network.  This paper aims to analyze existing condition of the road handling and installation of utilities and barriers to conducting synergy of program between the road handling and installation of utilities.  Data was collected using questionnaire survey to respondents that selected by purposive sampling method.  The result shows that currently, the synergy condition of   the road handling and installation of utilities in Denpasar City is only based on coordination among the stakeholder s regarding approval to install the utility network.  The barriers to integrated utility implementation include ineffective implementation of coordination and collaboration between related stakeholder s, ineffective involvement stakeholder in decision making, unavaibility of vision and mission of stakeholder s to alter the program,  stakeholder ‘s resistance to change, limited budget allocation on road handling lack of stakeholder ’s innovation, high cost of operational and maintenance,  and unavailability of stakeholder s who initiate the integrated program.   Key words : synergy, stakeholders, integrated management